Robotic-assisted laparoscopic management of mesenteric cysts in children - Chen, Qingjiang; Zhang, Shuhao; Luo, Wenjuan; Cai, Duote; Zhang, Yuebin; Huang, Zongwei; Xuan, Xiaoxiao; Xiong, Qixing; Gao, Zhigang (Frontiers in Pediatrics, 2023)
Background: Mesenteric cysts (MCs) are rare intra-abdominal masses in children, and laparoscopic complete cyst resection is still difficult. This study reviewed our experience in the diagnosis and management of MCs in our center, focusing on the clinical characteristics of MCs and the effectiveness of robotic assisted laparoscopic surgery. Methods: We conducted a retrospective analysis of the records of all patients diagnosed with MCs and managed with robotic assisted laparoscopic surgery in our center between February 2021 and August 2022. We analyzed demographic characteristics, clinical manifestations, preoperative imaging, surgical methods, postoperative complications, and final outcomes. Results: Totally, 12 consecutive patients with a mean age of 5.81±3.02 years were admitted. The most common symptom was abdominal pain (58.33%). Eight patients associated with cysts complications, including 5 cases of infection, 2 cases of volvulus and 1 case of hemorrhage. The mean size of cysts was 8.39±5.91cm. The cysts located in ileal mesentery in 8 cases, lesser curvature of stomach in 2 cases and colon mesentery in 2 cases. Solely cyst excision was performed in 8 cases, bowel resection en bloc with the cyst in 4 cases. All patients were performed robotic assisted laparoscopic surgery successfully, without conversion. The mean operation time was 106.17±33.74 minutes. Pathological results reported lymphangioma or lymphatic malformation in all patients. Two cases of chylous leakage were treated conservatively, no complications of peritoneal infection, anastomotic leakage and recurrence were observed. Conclusions: Mesenteric cysts should be removed promptly once the diagnosis confirmed to avoid cyst complications. For uncomplicated mesenteric cysts, laparoscopic cyst excision or cyst excision with bowel resection can be effectively performed in children, especially under the robot system.